Crecimiento, estado fitosanitario y calidad de Carapa guianensis "andiroba" en dos plantaciones del CIEFOR - Puerto Almendra, Loreto - Perú. 2021 - Sánchez Cruz, Veronica Anabel (2023)
The study was carried out in plantation 11 and 14 of CIEFOR - Puerto Almendra, evaluating Carapa guianensis seedlings installed in 2020. Plantation 11 presents the highest average increase in diameter with 4.10 mm. Regarding the height of the plants, plantation 14 presents the highest average increase with 62.4 cm. Likewise, plantation 11 presents a greater number of live plants with 177, which represents 88.5%; while plantation 14 presented 159 live plants (79.5%). On the other hand, plantation 14 presents a greater number of affected plants with 75% of the leaf area with a total of 44 plants while 60 plants have 50% of the leaf and stem area affected. Plantation 11 presents a Quality Coefficient from Good to Regular, while plantation 14 presented a Coefficient that varies from Bad to Regular. There is a significant difference in the increases in height in the plantation 14. It is necessary to carry out similar studies with other native forest species in CIEFOR - Puerto Almendra.